COOL SEASON FORAGE LEGUMES IN SOUTHWESTERN OF PARANÁ - SARTOR, Laércio Ricardo; ADAMI, Paulo Fernando; SOARES, André Brugnara; PITTA, Christiano Santos Rocha; MONTARDO, Daniel Portella; DALL’AGNOL, Miguel (Scientia Agraria, 2010)
Forage shortage during cool season at the southern Brazil is one of the most serious problems faced by farmers and due to it, cool season species represents an important alternative. The aim of this research was to verify the nutritional value and forage production of white clover (Trifolium repens), red clover (Trifolim pratense), birdsfoot trefoil (Lotus corniculatus) and annual Lotus (Lotus subbiflorus) genotypes. The experiment was carried out at Pato Branco the southwestern of Paraná state,Brazil and laid out as a random block design with four replications to the white and red clover genotypes and five replications to the Lotus genotypes. Forage production was high along the evaluated period, especially for birdsfoot trefoil, which showed an average production among its four genotypes of 9,757 kg ha-1 of DM, and as well as for to the red clover genotypes, which showed an average production of 8,184 kg ha-1 of DM. The birdsfoot trefoil genotypes San Gabriel Ijuí, San Gabriel and UFGRS highlighted as being the most productive among all the tested genotypes, although white and red clover showed better nutritional value when compared with birdsfoot trefoil. The white clover genotypes stood out by having the best nutritional value although with lower forage production than the other three species.